Dinâmica não linear e projeto de controle em sistemas de transporte vertical: comportamentos periódicos e caóticos - Santo, Douglas Roca [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The explosive growth of large urban centers allied to financial limited resources and pressure from increased demand, has forced the cities to develop prodominantly in the vertical direction with the construction of tall buildings (skyscrapers). To supply the demand of these constructions, the development of high speed elevators became a necessity. For high speed passenger's elevators, it is important to considerer passenger's safety and confort. Current research has focused attention on the horizontal and vertical vibration levels inside the cabin and oscillations of the elevator acceleration is usually caused by deformations and misalignments of the guide rails and disturbances caused by the air flow around the cabin. To improve passengers' travel quality, elevators should feature a good feature a good monitoring and control system in order to increase the positioning accuracy and set speed limits not to cause passengers discomfort, decreasing vertical and horizontal vibrations of the elevator cabin. This research aims on studuing and controlling the dynamic horizontal behavior of a three degree of freedom model of a vertical transportation system excited through guide rail deformations. The stiffness of the translational spring equivalent to the tilting motion of the cabin is modeled as a Duffing-type spring. Motivated by the necessity to improve passengers' comfort level, the State-Deéndent Ricatti Equation method is used as a strategy to control the horizontal vibrations and accelerations. Next, we perform extensive numerical simulations studied of the nonlinear behavior of the adopted mathematical model

O crescimento acelerado dos grandes centros urbanos aliado a recursos financeiros limitados e à pressão pelo aumento da demanda forçaram as cidades a desenvolverem-se predominantemente na direção vertical, com a construção de edifícios altos (arranha-céus). Para atender à demanda destas construções, o desenvolvimento de elevadores de alta velocidade tornou-se uma necessidade. Nesses elevadores, é necessário preocupar-se com o conforto e segurança dos passageiros. Pesquisas atuais têm dado atenção aos níveis de vibrações verticais e horizontais dentro da cabina e variações das acelerações do elevador. A vibração horizontal é causada normalmente por deformações e desalinhamento dos trilhos de guia e distúrbios devido ao fluxo de ar ao redor da cabina. Para melhorar a qualidade de viagem dos passageiros, os elevadores devem possuir um bom sistema de controle e monitoramento, com o objetivo de aumentar a precisão em seu posicionamento e fazer com que o limite de velocidade não cause desconforto nos passageiros, diminuindo as vibrações horizontais e verticais da cabina do elevador. Este trabalho tem como objetivo estudar e controlar o comportamento dinâmico horizontal de um modelo com três graus de liberdade de um sistema de transporte vertical, excitando através de deformações dos trilhos de guia. A rigidez da mola translacional equivale ao movimento pendular da cabina é modelada como uma mola do tipo Duffing. Motivado pela necessidade de aumentar o nível de conforto dos passageiros, o método equação de Ricatti Dependente de Estados é utilizado como estratégia para controlar as vibrações e acelerações horizontais. Por fim, foram realizados extensivos estudos sobre o comportamento dinâmico do modelo matemática adotado por meio de simulações numéricas
Nonlinear dynamic and control design in vertical transportation systems: periodic and chaotic behaviors
Keywords: Sistemas não lineares; Modelagem de processos; Vibração - Medição; Nonlinear systems